2005
DOI: 10.1007/s00380-005-0840-x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse correlation between soluble CD40 ligand and soluble CD40 is absent in patients with unstable angina

Abstract: The CD40/CD40 ligand (CD40L) system mediates inflammatory processes important in atherogenesis and plaque instability. The expression of CD40L on activated T cells was suppressed by soluble CD40 (sCD40) in vitro. However, the relationship between soluble CD40L (sCD40L) and sCD40 in unstable angina (UA) is still unknown. Thirty-seven consecutive patients with recent chest pain or discomfort were recruited. Patients with both Braunwald's class IB-IIIB and with coronary stenosis (or stenoses) of >75% were assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Weber et al (14) and Ahn et al (15) have reported that the reliable sample types for assessment of sCD40L were plasma when compared to serum. Tsuzuki et al (16) has observed no significant difference in serum sCD40L between UA and controls, in contrast to previously reported studies demonstrating increase in serum sCD40L in ACS patients. Ivandic et al (17) have reported significant increase of plasma sCD40L in ACS patients.…”
Section: Discussionmentioning
confidence: 59%
“…Weber et al (14) and Ahn et al (15) have reported that the reliable sample types for assessment of sCD40L were plasma when compared to serum. Tsuzuki et al (16) has observed no significant difference in serum sCD40L between UA and controls, in contrast to previously reported studies demonstrating increase in serum sCD40L in ACS patients. Ivandic et al (17) have reported significant increase of plasma sCD40L in ACS patients.…”
Section: Discussionmentioning
confidence: 59%
“…It is also deemed to be important in several inflammatory processes inducing VP. Expression of sCD40L may also be related to MMP-9 expression in atherosclerotic tissues [ 35 ]. CD40L will probably be a potential marker of instability of plaques [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matrix activity was observed in carcinogenesis, in some degenerative processes, and inflammatory conditions including atherogenesis. MMPs primarily MMP-9 has clinical significance in the serum of diabetic patients in inflammatory processes involving in plaque rupture and leading to acute coronary event with elevated levels [5][6][7][8][9][10][11][12][13] . MMP-9 is localized on the shoulders of plaque, a thin area which is suspected for rupture.…”
Section: Introductionmentioning
confidence: 99%